9(t-3)+36t=6(t+2)

Simple and best practice solution for 9(t-3)+36t=6(t+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(t-3)+36t=6(t+2) equation:


Simplifying
9(t + -3) + 36t = 6(t + 2)

Reorder the terms:
9(-3 + t) + 36t = 6(t + 2)
(-3 * 9 + t * 9) + 36t = 6(t + 2)
(-27 + 9t) + 36t = 6(t + 2)

Combine like terms: 9t + 36t = 45t
-27 + 45t = 6(t + 2)

Reorder the terms:
-27 + 45t = 6(2 + t)
-27 + 45t = (2 * 6 + t * 6)
-27 + 45t = (12 + 6t)

Solving
-27 + 45t = 12 + 6t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-6t' to each side of the equation.
-27 + 45t + -6t = 12 + 6t + -6t

Combine like terms: 45t + -6t = 39t
-27 + 39t = 12 + 6t + -6t

Combine like terms: 6t + -6t = 0
-27 + 39t = 12 + 0
-27 + 39t = 12

Add '27' to each side of the equation.
-27 + 27 + 39t = 12 + 27

Combine like terms: -27 + 27 = 0
0 + 39t = 12 + 27
39t = 12 + 27

Combine like terms: 12 + 27 = 39
39t = 39

Divide each side by '39'.
t = 1

Simplifying
t = 1

See similar equations:

| 3-(x-4)=2x+5 | | 12s^3+22s^2-70s=0 | | [10-5(x-2)]=(x+1) | | 5+5w=2+11w | | 6x-3=15-48 | | 3/x=9/2 | | 7/8*h=1/5 | | 35u^2-39u-14=0 | | 10.1+5.3=w | | 1=y(8y-4) | | 1,34x-5,4=x-3,7 | | 2*2=5y | | X^2+18+20=0 | | 4x=y(4x-4) | | -(14-2s)-(6s+4)=14 | | 4x^3+14x^2+166x+140=0 | | 4xy-4y-4x=0 | | 5r^2-6r+1=0 | | (31-0.5y)+(31-0.5y+4)+y=66 | | y=70+14(7) | | 2*40+3x=128 | | 73=x+0.32x | | 6x+ay=24 | | 2x+9x-4x=14+7 | | 0.03/9 | | 3x+ay=15 | | -2t^2+15t-15=0 | | x*x-v*v= | | 5x^2+21x-24=0 | | 10=x+0.32x | | 2(3x+1)-8=30 | | 2x+y=62 |

Equations solver categories